Where have all the flowers gone? A call for federal leadership in deer management in the United States - Blossey, Bernd; Hare, Darragh; Waller, Donald M. (Frontiers in Conservation Science, 2024)
Forests in the United States continue to lose biodiversity and many fail to regenerate due to high deer (family Cervidae) abundance. Declines in biodiversity and overall ecosystem health due to high deer populations increases prevalence of wildlife and human diseases associated with increasing tick abundances and decreases forest resilience and the ability to deliver benefits provided by healthy ecosystems. In the eastern and midwestern United States, white-tailed deer (Odocoileus virginianus) are the main stressor, while in the western U.S. elk (Cervus elaphus) and black-tailed and mule deer (Odocoileus hemionus) can become equally problematic. Federal and State Wildlife Agencies are responsible for environmental stewardship and management of deer, migratory and endangered species, yet they lack authority to address human health concerns or commercial interests (we acknowledge tribal authority to manage wildlife as an important contributor to conservation). Furthermore, State Wildlife Agencies have retained their traditional focus to manage wildlife for recreational hunters while neglecting their obligations to manage wildlife in the interest of all citizens, not special interest groups. The fragmented institutional arrangements between tribal, federal and state agencies, and widely scattered responsibilities for human health, environmental management and conservation, agriculture, and commerce among federal and state agencies has allowed deer impacts to reach the level of a nationwide conservation and human health crisis. Since local, regional, and statewide initiatives have failed to provide appropriate remedies, we consider federal leadership essential to allow integration across different disciplines, policy domains, and biota, as well as across different regions and habitats. We recommend the development of a National Strategy that builds strong collaborative efforts and diverse and inclusive relationships across environmental, human health and economic interests that reach beyond state boundaries to have a chance to comprehensively address the deer, human health, forest, and conservation crises. A well-coordinated and collaborative approach may overcome traditional turf battles between tribal, state and federal interests by recognizing joint responsibilities and obligations to manage wild life as a public trust resource. Such a collective approach can protect species before they are endangered — otherwise both environmental and human health will continue to decline.